2023
DOI: 10.26434/chemrxiv-2023-pb9pp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing the Organohalogen Iceberg: Extractable, multi-halogen mass balance determination in municipal wastewater treatment plant sludge

Abstract: The large number and diversity of organohalogen compounds (OHCs) occurring in the environment poses a grand challenge to analytical chemists. Since no single targeted method can identify and quantify all OHCs, the size of the OHC iceberg may be underestimated. We sought to address this problem in municipal wastewater treatment plant (WWTP) sludge by quantifying the unidentified fraction of the OHC iceberg using targeted analyses of major OHCs together with measurements of total- and extractable (organo)halogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Our initial targeted analysis reported six out of 16 target perfluoroalkyl acids (PFOS, PFDA, PFUnDA, PFDoDA, PFTrDA, PFTeDA; ∑ 16 PFAS = 12.5 ng/g) which together accounted for ∼2% of the EOF. Suspect screening in the present study revealed an additional seven “conventional” PFAS: 5:3 FTCA (CL1), 6:2 diPAP (CL1), EtFOSAA (CL1), MeFOSAA (CL1), and H-PFOS (CL4), which occurred at concentrations ranging from 0.07 to 11.9 ng/g dw, and 8:2 diPAP and 6:2/8:2 diPAP (both CL1), which were detectable but below quantification limits (Table ; Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our initial targeted analysis reported six out of 16 target perfluoroalkyl acids (PFOS, PFDA, PFUnDA, PFDoDA, PFTrDA, PFTeDA; ∑ 16 PFAS = 12.5 ng/g) which together accounted for ∼2% of the EOF. Suspect screening in the present study revealed an additional seven “conventional” PFAS: 5:3 FTCA (CL1), 6:2 diPAP (CL1), EtFOSAA (CL1), MeFOSAA (CL1), and H-PFOS (CL4), which occurred at concentrations ranging from 0.07 to 11.9 ng/g dw, and 8:2 diPAP and 6:2/8:2 diPAP (both CL1), which were detectable but below quantification limits (Table ; Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Closing the Organofluorine Mass Balance in Municipal WWTP Sludge. While suspect screening together with (semi)quantification increased the percentage of known EOF from ∼2% 22 to ∼27% in Henriksdal WWTP sludge, a large proportion (∼73%) of the EOF remains unidentified. The source of the remaining unidentified organofluorine is unclear, but may include additional pharmaceuticals, pesticides and TPs not captured by our workflow.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations